Effectiveness of neem leaf extract (Azadirachta Indica A. Juss) against C.albicans on acrylic resin plates: Efektivitas ekstrak daun mimba (Azadirachta Indica A. Juss) terhadap C.albicans pada plat resin akrilik - Helena Jelita; Sintha Nugrahini (Makassar Dental Journal PDGI Makassar, 2021)
Denture stomatitis, the main cause of which is Candida species, especially C.albicans, is an inflammation of the oral mucosa of removable denture users which can be associated with reactions to oral biofilms, denture materials, or trauma due to dentur-es. The use of chemicals as denture cleaners can increase the roughness of the base surface, so that herbal ingredients can be used as alternative denture cleaners. Neem leaves (Azadirachta Indica A. Juss) contain active ingredients that can kill bacte-ria and fungi, in the form of azadirachtin, salannin, meliantriol, and nimbin as well as tannin compounds, saponins, flavonoids and terpenoids which have antifungal mechanisms. This research was aimed to determine the effectiveness of neem leaf extract against C.albicans on acrylic resin denture plates. The sample of this posttest only control group design study consisted of 24 acrylic resin plates contaminated with C.albicans suspension. After that, the samples were immersed in 4 groups of disinfectant solutions, namely 5% EDM, 10% EDM, aquadest and Polident® for 30 minutes. The number of C.albicans colonies was tested by Kruskal Wallis and U Mann Whitney. The results showed that the mean C.albicans colony in the EDM 5%, 10% EDM, aquadest and Polident® groups were 21.50 CFU/mL, 15.50 CFU/mL, 27.50 CFU/mL, 6.50 CFU/mL respectively. Neem leaf extract significantly decreased the number of C.albicans colonies (p <0.005). It was concluded that the higher the EDM con-centration, the greater its ability to reduce the number of C.albicans colonies.